A rapid national survey of terrestrial and semi-aquatic mammals using environmental DNA metabarcoding - Holly A. Broadhurst; Elin E. Smith; Jake M. Jackman; Robert Raynor; Claire Howe; Naiara Guimarães Sales; Allan D. McDevitt (Mammalian Biology, 2026)
Assessing the distribution and diversity of terrestrial and semi-aquatic mammals is fundamental for effective conservation efforts. Environmental DNA (eDNA) metabarcoding has emerged as a rapid and cost-effective method for surveying mammals. It has promising avenues for conducting national surveys and enabling comprehensive assessments of mammalian populations across diverse habitats. We collected eDNA samples from 60 water systems across six regions in England (from north to south), United Kingdom, over a period of up to four days in each region. We detected 26 mammals from five taxonomic orders across all sampling locations, recovering 53–89% of the known mammal community in each region. Our findings underscore the feasibility of utilising eDNA metabarcoding for rapidly surveying mammal populations on a national scale, potentially complementing data from existing surveys/records or implementing in data deficient regions. However, challenges remain for surveying certain species using this method, with varying levels of detectability of key species (e.g. otters) across regions.

Genetic engineering of dinoflagellate algae and the lethality of an introduced plastid terminal oxidase - I.C. Nimmo; C.E. Evans; L.M. Li; A.C. Barbrook; K. Geisler; F.H. Kleiner; A. Scarampi; D. Kosmützky; L.T. Wey; R.G. Dorrell; C.J. Howe; R.E.R. Nisbet (Protist, 2026)

Carbon stock and flux predictions in second-growth Sitka-spruce and western hemlock dominated stands of Southeast Alaska - Dryw A. Jones; David V. D’Amore; Kellen N. Nelson; Frances Biles; Michael C. Howe (Forest Ecology and Management, 2026)

Adsorption of per- and polyfluoroalkyl substances (PFAS) by quaternary ammonium and fluorine-functionalized macrocyclic sorbents: A comprehensive experimental and simulation study - Yilang Sun; Ameevardhan Singh Patyal; George Hana; Ke Wu; Isreq Real; Chao Zhou; Jennifer L. Guelfo; Joshua D. Howe; Yuexiao Shen (Water Research, 2026)

Working memory processes and the histamine-3 receptor in schizophrenia: a [11C]MK-8278 PET-fMRI study - Atheeshaan Arumuham; Ekaterina Shatalina; Matthew M. Nour; Mattia Veronese; Ellis Chika Onwordi; Stephen J. Kaar; Sameer Jauhar; Eugenii A. Rabiner; Oliver D. Howes (Psychopharmacology, 2025)
Rationale Working memory impairment is a prominent feature of schizophrenia which predicts clinical and functional outcomes. Preclinical data suggest histamine-3 receptor (H3R) expression in cortical pyramidal neurons may have a role in working memory, and post-mortem data has found disruptions of H3R expression in schizophrenia. Objectives We examined the role of H3R in vivo to elucidate its role on working memory impairment in schizophrenia. Methods We used positron emission tomography (PET) with the selective H3R radioligand [ 11 C]MK-8278 to measure H3R availability, and employed a task during functional magnetic resonance imaging (fMRI) to assess working memory-evoked brain activation and cognitive task performance, in patients with schizophrenia ( n = 12) and matched healthy volunteers ( n = 12). We assessed the relationship between H3R availability and both task performance and working memory-evoked brain activation in regions of interest (ROIs), including the anterior cingulate cortex (ACC) and dorsolateral prefrontal cortex (DLPFC). Results Patients with schizophrenia showed a strong positive correlation, after corrections for multiple comparisons, between ACC H3R availability and task performance (rho = 0.73, p = 0.007), which was absent in the control group (rho = 0.03, p = 0.94). Further ROI analysis did not find a significant relationship between H3R availability and working memory-evoked brain activation. Conclusions These results provide support for the role of H3R on working memory processes in patients with schizophrenia.

Developing a consistent model for predicting equilibration in polymeric passive samplers across various HOC classes in sediment pore water - Ashkan Alborzi; Moein Hajian Z.D.; Uriel Garza-Rubalcava; Tariq Hussain; M.D. Rashedul Islam; Joshua D. Howe; Danny Reible (Chemosphere, 2024)

Relative humidity, temperature, and hypertensive disorders of pregnancy: Findings from the Project Viva cohort - Christina M. Howe; Brent A. Coull; Stefania Papatheodorou; Heike Luttmann-Gibson; Sheryl L. Rifas-Shiman; Ander Wilson; Itai Kloog; Qian Di; Antonella Zanobetti; Petros Koutrakis; Joel D. Schwartz; Emily Oken; et al. (Environmental Research, 2024)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

Universal or targeted approaches? an experiment about heat risk messaging - Yajie Li; Peter D. Howe (Natural Hazards, 2023)

Salt marsh vegetation change during a half-century of experimental nutrient addition and climate-driven controls in Great Sippewissett Marsh - I. Valiela; K. Chenoweth; J. Lloret; J. Teal; B. Howes; D. Goehringer Toner (Science of The Total Environment, 2023)

Investigating geological records of tsunamis in Western Thailand with environmental DNA - Wenshu Yap; Adam D. Switzer; Chris Gouramanis; Benjamin P. Horton; Ezequiel M. Marzinelli; Winona Wijaya; Yu Ting Yan; Dale Dominey-Howes; Maurizio Labbate; Kruawun Jankaew; Federico M. Lauro (Marine Geology, 2023)

Geographic and demographic variation in worry about extreme heat and COVID-19 risk in summer 2020 - Peter D. Howe; Olga V. Wilhelmi; Mary H. Hayden; Cassandra O'Lenick (Applied Geography, 2023)

Brain volume in chronic ketamine users — relationship to sub-threshold psychotic symptoms and relevance to schizophrenia - Robert A. Chesters; Fiona Pepper; Celia Morgan; Jonathan D. Cooper; Oliver D. Howes; Anthony C. Vernon; James M. Stone (Psychopharmacology, 2022)
Rationale Ketamine may model aspects of schizophrenia arising through NMDA receptor activity deficits. Although acute ketamine can induce effects resembling both positive and negative psychotic symptoms, chronic use may be a closer model of idiopathic psychosis. Objectives We tested the hypotheses that ketamine users had lower brain volumes, as measured using MRI, and greater sub-threshold psychotic symptoms relative to a poly-drug user control group. Methods Ketamine users (n = 17) and poly-drug using controls (n = 19) were included in the study. All underwent volumetric MRI imaging and measurement of sub-threshold psychotic symptoms using the Comprehensive Assessment of At-Risk Mental State (CAARMS). Freesurfer was used to analyse differences in regional brain volume, cortical surface area and thickness between ketamine users and controls. The relationship between CAARMS ratings and brain volume was also investigated in ketamine users. Results Ketamine users were found to have significantly lower grey matter volumes of the nucleus accumbens, caudate nucleus, cerebellum and total cortex (FDR p < 0.05; Cohen’s d = 0.36–0.75). Within the cortex, ketamine users had significantly lower grey matter volumes within the frontal, temporal and parietal cortices (Cohen’s d 0.7–1.31; FDR p < 0.05). They also had significantly higher sub-threshold psychotic symptoms (p < 0.05). Frequency of ketamine use showed an inverse correlation with cerebellar volume (p < 0.001), but there was no relationship between regional brain volumes and sub-threshold psychotic symptoms. Conclusions Chronic ketamine use may cause lower grey matter volumes as well as inducing sub-threshold psychotic symptoms, although these likely arise through distinct mechanisms.

Adenosine A2A receptor in schizophrenia: an in vivo brain PET imaging study - Tiago Reis Marques; Sridhar Natesan; Eugenii A. Rabiner; Graham E. Searle; Roger Gunn; Oliver D. Howes; Shitij Kapur (Psychopharmacology, 2022)
Adenosine A 2A receptors are highly enriched in the basal ganglia system, a region that is functionally implicated in schizophrenia. Preclinical evidence suggests a cross-regulation between adenosine A 2A and dopamine D 2 receptors in this region and that it is linked to the sensitization of the dopamine system. However, the relationship between A 2A receptor availability and schizophrenia has not been directly examined in vivo in patients with this disorder. To investigate, using positron emission tomography (PET), the availability of A 2A receptors in patients diagnosed with schizophrenia in comparison to matched healthy controls. A 2A receptor availability was measured using the PET tracer [ 11 C]SCH442416. Twelve male patients with chronic schizophrenia were compared to 13 matched healthy subjects. All patients were medicated with antipsychotics and none presented with any motor or extrapyramidal symptoms. Binding potential (BP ND ), a ratio measure between specific and non-specific tracer uptake, were compared between the groups for the caudate, putamen, accumbens and globus pallidum. There was no differences between A 2A receptor binding potential (BP ND ) of schizophrenia patients in the caudate ( p = 0.16), putamen ( p = 0.86), accumbens ( p = 0.44) and globus pallidum ( p = 0.09) to that of matched healthy subjects. There was also no significant correlation between [11C]SCH442416 binding and severity of psychotic symptoms ( p = 0.2 to 0.82) or antipsychotic dosage ( p = 0.13 to 0.34). By showing that A2A receptor availability in medicated patients with chronic male schizophrenia is not different than in healthy controls, this study does not support the primary role of this receptor in the pathogenesis of schizophrenia.

The effects of AUT00206, a novel Kv3.1/3.2 potassium channel modulator, on task-based reward system activation: a test of mechanism in schizophrenia - Stephen J. Kaar; Ilinca Angelescu; Matthew M. Nour; Tiago Reis Marques; Alice Sharman; Anil Sajjala; John Hutchison; Philip McGuire; Charles Large; Oliver D. Howes (Psychopharmacology, 2022)
The pathophysiology of schizophrenia involves abnormal reward processing, thought to be due to disrupted striatal and dopaminergic function. Consistent with this hypothesis, functional magnetic resonance imaging (fMRI) studies using the monetary incentive delay (MID) task report hypoactivation in the striatum during reward anticipation in schizophrenia. Dopamine neuron activity is modulated by striatal GABAergic interneurons. GABAergic interneuron firing rates, in turn, are related to conductances in voltage-gated potassium 3.1 (Kv3.1) and 3.2 (Kv3.2) channels, suggesting that targeting Kv3.1/3.2 could augment striatal function during reward processing. Here, we studied the effect of a novel potassium Kv3.1/3.2 channel modulator, AUT00206, on striatal activation in patients with schizophrenia, using the MID task. Each participant completed the MID during fMRI scanning on two occasions: once at baseline, and again following either 4 weeks of AUT00206 or placebo treatment. We found a significant inverse relationship at baseline between symptom severity and reward anticipation-related neural activation in the right associative striatum ( r = -0.461, p = 0.035). Following treatment with AUT00206, there was a significant increase in reward anticipation-related activation in the left associative striatum (t (13) = 4.23, peak-level p (FWE) < 0.05)), but no significant effect in the ventral striatum. This provides preliminary evidence that the Kv3.1/3.2 potassium channel modulator, AUT00206, may address reward-related striatal abnormalities in schizophrenia.

Test–retest reliability of arterial spin labelling for cerebral blood flow in older adults with small vessel disease - Lauren R. Binnie; Mathilde M. H. Pauls; Philip Benjamin; Mohani-Preet K. Dhillon; Shai Betteridge; Brian Clarke; Rita Ghatala; Fearghal A. H. Hainsworth; Franklyn A. Howe; Usman Khan; Christina Kruuse; Jeremy B. Madigan; et al. (Translational Stroke Research, 2022)
Cerebral small vessel disease (SVD) is common in older people and is associated with lacunar stroke, white matter hyperintensities (WMH) and vascular cognitive impairment. Cerebral blood flow (CBF) is reduced in SVD, particularly within white matter. Here we quantified test–retest reliability in CBF measurements using pseudo-continuous arterial spin labelling (pCASL) in older adults with clinical and radiological evidence of SVD (N=54, mean (SD): 66.9 (8.7) years, 15 females/39 males). We generated whole-brain CBF maps on two visits at least 7 days apart (mean (SD): 20 (19), range 7-117 days). Test–retest reliability for CBF was high in all tissue types, with intra-class correlation coefficient [95%CI]: 0.758 [0.616, 0.852] for whole brain, 0.842 [0.743, 0.905] for total grey matter, 0.771 [0.636, 0.861] for deep grey matter (caudate-putamen and thalamus), 0.872 [0.790, 0.923] for normal-appearing white matter (NAWM) and 0.780 [0.650, 0.866] for WMH (all p<0.001). ANCOVA models indicated significant decline in CBF in total grey matter, deep grey matter and NAWM with increasing age and diastolic blood pressure (all p<0.001). CBF was lower in males relative to females (p=0.013 for total grey matter, p=0.004 for NAWM). We conclude that pCASL has high test–retest reliability as a quantitative measure of CBF in older adults with SVD. These findings support the use of pCASL in routine clinical imaging and as a clinical trial endpoint. All data come from the PASTIS trial, prospectively registered at: https://eudract.ema.europa.eu (2015-001235-20, registered 13/05/2015), http://www.clinicaltrials.gov (NCT02450253, registered 21/05/2015).

Striatal dopamine synthesis capacity and its association with negative symptoms upon resolution of positive symptoms in first-episode schizophrenia and delusional disorder - Stephanie M. Y. Wong; Y. N. Suen; Charlotte W. C. Wong; Sherry K. W. Chan; Christy L. M. Hui; W. C. Chang; Edwin H. M. Lee; Calvin P. W. Cheng; Garrett C. L. Ho; Gladys Goh Lo; Eric Y. L. Leung; Paul K. M. Au Yeung; et al. (Psychopharmacology, 2022)

Exploring the Use of Seabirds as a Dynamic Ocean Management Tool to Mitigate Anthropogenic Risk to Large Whales - Tammy L. Silva; Kevin D. Powers; Jooke Robbins; Regina Asmutis-Silvia; Timothy V. N. Cole; Alex N. Hill; Laura J. Howes; Charles A. Mayo; Dianna Schulte; Michael A. Thompson; Linda J. Welch; Alexandre N. Zerbini; et al. (Frontiers in Marine Science, 2022)
Vessel strike and entanglement in fishing gear are global threats to large whales. United States management actions to reduce human-induced serious injury and mortality to large whales have been inadequate, partially due to static, spatial protection schemes that fail to adjust to distribution shifts of highly mobile animals. Whale conservation would benefit from dynamic ocean management, but few tools exist to inform dynamic approaches. Seabirds are often found in association with whales and can be tagged at lower cost and in higher numbers than whales. We explored the use of satellite-tagged seabirds (great shearwaters) as dynamic ocean management tools for near real-time identification of habitats where humpback and North Atlantic right whales aggregate, potentially increasing anthropogenic risk. We identified shearwater habitat use areas in the Gulf of Maine with 50% kernel density utilization distributions at yearly, monthly, and weekly scales using satellite-telemetry data from 2013-2018. We quantified overlap using whale sightings and whale satellite telemetry data at two spatial scales: Stellwagen Bank National Marine Sanctuary and the Gulf of Maine. Within the sanctuary, shearwaters overlapped with >50% of humpback sightings in 4 of 6 (67%) years, 15 of 23 (65%) months, and 50 of 89 (56%) of weeks. At the Gulf of Maine scale, shearwater use areas overlapped >50% of humpback sightings in 5 of 6 years (83%) and 16 of 22 (73%) months, and encompassed humpback 50% utilization distributions (based on satellite telemetry) in 2 of 3 (66%) years and 7/12 (58%) months analyzed. Overlap between shearwaters and right whales was much lower, with >50% overlap in only 1 of 6 (17%) years and 3 of 23 (13%) months. These initial results demonstrate that satellite-tagged shearwaters can be indicators of humpback whale habitat use in both space and time. With further study, tagged shearwaters may provide near-real time information necessary to operationalize dynamic management to mitigate human impacts on humpback whales.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The acute effects of cannabidiol on emotional processing and anxiety: a neurocognitive imaging study - Michael A. P. Bloomfield; Yumeya Yamamori; Chandni Hindocha; Augustus P. M. Jones; Jocelyn L. L. Yim; Hannah R. Walker; Ben Statton; Matthew B. Wall; Rachel H. Lees; Oliver D. Howes; Valerie H. Curran; Jonathan P. Roiser; et al. (Psychopharmacology, 2022)
Rationale There is growing interest in the therapeutic potential of cannabidiol (CBD) across a range of psychiatric disorders. CBD has been found to reduce anxiety during experimentally induced stress in anxious individuals and healthy controls. However, the mechanisms underlying the putative anxiolytic effects of CBD are unknown. Objectives We sought to investigate the behavioural and neural effects of a single dose of CBD vs. placebo on a range of emotion-related measures to test cognitive-mechanistic models of its effects on anxiety. Methods We conducted a randomised, double-blind, placebo-controlled, crossover, acute oral challenge of 600 mg of CBD in 24 healthy participants on emotional processing, with neuroimaging (viewing emotional faces during functional magnetic resonance imaging) and cognitive (emotional appraisal) measures as well as subjective response to experimentally induced anxiety. Results CBD did not produce effects on brain responses to emotional faces and cognitive measures of emotional processing, or modulate experimentally induced anxiety, relative to placebo. Conclusions Given the rising popularity of CBD for its putative medical benefits, these findings question whether further research is warranted to investigate the clinical potential of CBD for the treatment of anxiety disorders.

A dual compartment cuvette system for correcting scattering in whole-cell absorbance spectroscopy of photosynthetic microorganisms - John R. D. Hervey; Paolo Bombelli; David J. Lea-Smith; Alan K. Hulme; Nathan R. Hulme; Atvinder K. Rullay; Robert Keighley; Christopher J. Howe (Photosynthesis Research, 2022)
Absorption spectroscopy is widely used to determine absorption and transmission spectra of chromophores in solution, in addition to suspensions of particles, including micro-organisms. Light scattering, caused by photons deflected from part or all of the cells or other particles in suspension, results in distortions to the absorption spectra, lost information and poor resolution. A spectrophotometer with an integrating sphere may be used to alleviate this problem. However, these instruments are not universally available in biology laboratories, for reasons such as cost. Here, we describe a novel, rapid, and inexpensive technique that minimises the effect of light scattering when performing whole-cell spectroscopy. This method involves using a custom made dual compartment cuvette containing titanium dioxide in one chamber as a scattering agent. Measurements were conducted of a range of different photosynthetic micro-organisms of varying cell size and morphology, including cyanobacteria, eukaryotic microalgae and a purple non-sulphur bacterium. A concentration of 1 mg ml −1 titanium dioxide, using a spectrophotometer with a slit width of 5 nm, produced spectra for cyanobacteria and microalgae similar (1–4% difference) to those obtained using an integrating sphere. The spectrum > 520 nm was similar to that with an integrating sphere with the purple non-sulphur bacterium. This system produced superior results to those obtained using a recently reported method, the application of the diffusing agent, Scotch™ Magic tape, to the side of the cuvette. The protocol can be completed in an equivalent period of time to standard whole-cell absorbance spectroscopy techniques, and is, in principle, suitable for any dual-beam spectrophotometer.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Impacts of zebra mussels (Dreissena polymorpha) on isotopic niche size and niche overlap among fish species in a mesotrophic lake - Alexandra L. Morrison; Mary A. Thelen; Sarah E. Howe; Kyle D. Zimmer; Brian R. Herwig; David F. Staples; Margaret C. McEachran (Biological Invasions, 2021)

Challenges in CNS drug development and the role of imaging - Oliver D. Howes; Mitul A. Mehta (Psychopharmacology, 2021)

Historic and Modern Approaches for the Discovery of Abandoned Wells for Methane Emissions Mitigation in Oil Creek State Park, Pennsylvania - Patricia M. B. Saint-Vincent; James I. Sams; Mumbi Mundia-Howe; Matthew D. Reeder; Garret A. Veloski; Natalie J. Pekney (Environmental Management, 2021)

Publisher Correction to: Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

An optimisation-based iterative approach for speckle tracking echocardiography - Neda Azarmehr; Xujiong Ye; Joseph D. Howes; Benjamin Docking; James P. Howard; Darrel P. Francis; Massoud Zolgharni (Medical & Biological Engineering & Computing, 2020)
Speckle tracking is the most prominent technique used to estimate the regional movement of the heart based on echocardiograms. In this study, we propose an optimised-based block matching algorithm to perform speckle tracking iteratively. The proposed technique was evaluated using a publicly available synthetic echocardiographic dataset with known ground-truth from several major vendors and for healthy/ischaemic cases. The results were compared with the results from the classic (standard) two-dimensional block matching. The proposed method presented an average displacement error of 0.57 pixels, while classic block matching provided an average error of 1.15 pixels. When estimating the segmental/regional longitudinal strain in healthy cases, the proposed method, with an average of 0.32 ± 0.53, outperformed the classic counterpart, with an average of 3.43 ± 2.84. A similar superior performance was observed in ischaemic cases. This method does not require any additional ad hoc filtering process. Therefore, it can potentially help to reduce the variability in the strain measurements caused by various post-processing techniques applied by different implementations of the speckle tracking.

Symbiont community diversity is more variable in corals that respond poorly to stress - Lauren I. Howe‐Kerr; Benedicte Bachelot; Rachel M. Wright; Carly D. Kenkel; Line K. Bay; Adrienne M. S. Correa (Global Change Biology, 2020)
Coral reefs are declining globally as climate change and local water quality press environmental conditions beyond the physiological tolerances of holobionts—the collective of the host and its microbial symbionts. To assess the relationship between symbiont composition and holobiont stress tolerance, community diversity metrics were quantified for dinoflagellate endosymbionts (Family: Symbiodiniaceae) from eight Acropora millepora genets that thrived under or responded poorly to various stressors. These eight selected genets represent the upper and lower tails of the response distribution of 40 coral genets that were exposed to four stress treatments (and control conditions) in a 10‐day experiment. Specifically, four ‘best performer’ coral genets were analyzed at the end of the experiment because they survived high temperature, high p CO 2 , bacterial exposure, or combined stressors, whereas four ‘worst performer’ genets were characterized because they experienced substantial mortality under these stressors. At the end of the experiment, seven of eight coral genets mainly hosted Cladocopium symbionts, whereas the eighth genet was dominated by both Cladocopium and Durusdinium symbionts. Symbiodiniaceae alpha and beta diversity were higher in worst performing genets than in best performing genets. Symbiont communities in worst performers also differed more after stress exposure relative to their controls (based on normalized proportional differences in beta diversity), than did best performers. A generalized joint attribute model estimated the influence of host genet and treatment on Symbiodiniaceae community composition and identified strong associations among particular symbionts and host genet performance, as well as weaker associations with treatment. Although dominant symbiont physiology and function contribute to host performance, these findings emphasize the importance of symbiont community diversity and stochasticity as components of host performance. Our findings also suggest that symbiont community diversity metrics may function as indicators of resilience and have potential applications in diverse disciplines from climate change adaptation to agriculture and medicine.

Leveraging a Landscape-Level Monitoring and Assessment Program for Developing Resilient Shorelines throughout the Laurentian Great Lakes - Donald G. Uzarski; Douglas A. Wilcox; Valerie J. Brady; Matthew J. Cooper; Dennis A. Albert; Jan J. H. Ciborowski; Nicholas P. Danz; Anne Garwood; Joseph P. Gathman; Thomas M. Gehring; Greg P. Grabas; Robert W. Howe; et al. (Wetlands, 2019)

The effects of cannabinoid 1 receptor compounds on memory: a meta-analysis and systematic review across species - Faith Borgan; Katherine Beck; Emma Butler; Robert McCutcheon; Mattia Veronese; Anthony Vernon; Oliver D. Howes (Psychopharmacology, 2019)

Transforming growth factor-β promotes basement membrane fibrosis, alters perivascular cerebrospinal fluid distribution, and worsens neurological recovery in the aged brain after stroke - Matthew D. Howe; J. Weldon Furr; Yashasvee Munshi; Meaghan A. Roy-O’Reilly; Michael E. Maniskas; Edward C. Koellhoffer; John d’Aigle; Lauren H. Sansing; Louise D. McCullough; Akihiko Urayama (GeroScience, 2019)

Altered glutamatergic response and functional connectivity in treatment resistant schizophrenia: the effect of riluzole and therapeutic implications - Toby Pillinger; Maria Rogdaki; Robert A. McCutcheon; Pamela Hathway; Alice Egerton; Oliver D. Howes (Psychopharmacology, 2019)

Tobacco smoking and dopaminergic function in humans: a meta-analysis of molecular imaging studies - Abhishekh H. Ashok; Yuya Mizuno; Oliver D. Howes (Psychopharmacology, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Perceptions of seasonal weather are linked to beliefs about global climate change: evidence from Norway - Peter D. Howe (Climatic Change, 2018)

Correction to: The spatial distribution of Republican and Democratic climate opinions at state and local scales - Matto Mildenberger; Jennifer R. Marlon; Peter D. Howe; Anthony Leiserowitz (Climatic Change, 2018)

Generation of transgenic goats by pronuclear microinjection: a retrospective analysis of a commercial operation (1995–2012) - W. Gavin; S. Blash; N. Buzzell; D. Pollock; L. Chen; N. Hawkins; J. Howe; K. Miner; J. Pollock; C. Porter; M. Schofield; Y. Echelard; et al. (Transgenic Research, 2018)

The spatial distribution of Republican and Democratic climate opinions at state and local scales - Matto Mildenberger; Jennifer R. Marlon; Peter D. Howe; Anthony Leiserowitz (Climatic Change, 2017)

Standardized Measures of Coastal Wetland Condition: Implementation at a Laurentian Great Lakes Basin-Wide Scale - Donald G. Uzarski; Valerie J. Brady; Matthew J. Cooper; Douglas A. Wilcox; Dennis A. Albert; Richard P. Axler; Peg Bostwick; Terry N. Brown; Jan J. H. Ciborowski; Nicholas P. Danz; Joseph P. Gathman; Thomas M. Gehring; et al. (Wetlands, 2017)

The key role played by charge in the interaction of cytochrome c with cardiolipin - Federica Sinibaldi; Lisa Milazzo; Barry D. Howes; Maria Cristina Piro; Laura Fiorucci; Fabio Polticelli; Paolo Ascenzi; Massimo Coletta; Giulietta Smulevich; Roberto Santucci (JBIC Journal of Biological Inorganic Chemistry, 2017)

Semiautomatic and Automatic Cooperative Inversion of Seismic and Magnetotelluric Data - Cuong V. A. Le; Brett D. Harris; Andrew M. Pethick; Eric M. Takam Takougang; Brendan Howe (Surveys in Geophysics, 2016)

Fronto-limbic engagement during moral processing in stimulant users - N. J. Blackwood; O. D. Howes (Psychopharmacology, 2016)

Revision and improvement of the PTVA-3 model for assessing tsunami building vulnerability using “international expert judgment”: introducing the PTVA-4 model - F. Dall’Osso; D. Dominey-Howes; C. Tarbotton; S. Summerhayes; G. Withycombe (Natural Hazards, 2016)

Influences of Natural and Anthropogenic Factors and Tidal Restoration on Terrestrial Arthropod Assemblages in West Coast North American Estuarine Wetlands - Aaron T. David; Pascale A. L. Goertler; Stuart H. Munsch; Brittany R. Jones; Charles A. Simenstad; Jason D. Toft; Jeffery R. Cordell; Emily R. Howe; Ayesha Gray; Michael P. Hannam; William Matsubu; Erin E. Morgan (Estuaries and Coasts, 2016)

Targeting glutamate to treat schizophrenia: lessons from recent clinical studies - Katherine Beck; Daniel C Javitt; Oliver D Howes (Psychopharmacology, 2016)

Immune influences on the brain: new findings and implications for treatment - Theodora Duka; Neil A. Harrison; Oliver D. Howes (Psychopharmacology, 2016)

Stress and neuroinflammation: a systematic review of the effects of stress on microglia and the implications for mental illness - Marilia A. Calcia; David R. Bonsall; Peter S. Bloomfield; Sudhakar Selvaraj; Tatiana Barichello; Oliver D. Howes (Psychopharmacology, 2016)

Autoantibodies to central nervous system neuronal surface antigens: psychiatric symptoms and psychopharmacological implications - T. A. Pollak; K. Beck; S. R. Irani; O. D. Howes; A. S. David; P. K. McGuire (Psychopharmacology, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Barriers to Effective Genome Editing of Haematopoietic Stem Cells - Steven J. Howe; Michael D. Milsom (Current Stem Cell Reports, 2016)

Further human evidence for striatal dopamine release induced by administration of ∆9-tetrahydrocannabinol (THC): selectivity to limbic striatum - Matthijs G. Bossong; Mitul A. Mehta; Bart N. M. van Berckel; Oliver D. Howes; René S. Kahn; Paul R. A. Stokes (Psychopharmacology, 2015)

Using extended pedigrees to identify novel autism spectrum disorder (ASD) candidate genes - Marc Woodbury-Smith; Andrew D. Paterson; Bhooma Thiruvahindrapduram; Anath C. Lionel; Christian R. Marshall; Daniele Merico; Bridget A. Fernandez; Eric Duku; James S. Sutcliffe; Irene O’Conner; Christina Chrysler; Ann Thompson; et al. (Human Genetics, 2015)

Development of an Integrated Surface Stimulation Device for Systematic Evaluation of Wound Electrotherapy - D. S. Howe; J. Dunning; C. Zorman; S. L. Garverick; K. M. Bogie (Annals of Biomedical Engineering, 2015)

Mapping the shadow of experience of extreme weather events - Peter D. Howe; Hilary Boudet; Anthony Leiserowitz; Edward W. Maibach (Climatic Change, 2014)

Public perceptions of rainfall change in India - Peter D. Howe; Jagadish Thaker; Anthony Leiserowitz (Climatic Change, 2014)

The relationship between reward and punishment processing and the 5-HT1A receptor as shown by PET - Paul Faulkner; Sudhakar Selvaraj; Alex Pine; Oliver D. Howes; Jonathan P. Roiser (Psychopharmacology, 2014)

The link between dopamine function and apathy in cannabis users: an [18F]-DOPA PET imaging study - Michael A. P. Bloomfield; Celia J. A. Morgan; Shitij Kapur; H. Valerie Curran; Oliver D. Howes (Psychopharmacology, 2014)

Erratum to: Glutamate, N-acetyl aspartate and psychotic symptoms in chronic ketamine users - James M. Stone; Fiona Pepper; Johnson Fam; Hannah Furby; Emer Hughes; Celia Morgan; Oliver D. Howes (Psychopharmacology, 2014)

Glutamate, N-acetyl aspartate and psychotic symptoms in chronic ketamine users - James M. Stone; Fiona Pepper; Johnson Fam; Hannah Furby; Emer Hughes; Celia Morgan; Oliver D. Howes (Psychopharmacology, 2014)

Mind the mortality gap: the importance of metabolic function in mental illnesses - Oliver D. Howes; Katherine Beck (Psychopharmacology, 2013)

Replacement of Phragmites australis by Spartina alterniflora: The Role of Competition and Salinity - D. L. Medeiros; D. S. White; B. L. Howes (Wetlands, 2013)

Knee extensor strength differences in obese and healthy-weight 10-to 13-year-olds - Margarita D. Tsiros; Alison M. Coates; Peter R. C. Howe; Paul N. Grimshaw; Jeff Walkley; Anthony Shield; Richard Mallows; Andrew P. Hills; Masaharu Kagawa; Sarah Shultz; Jonathan D. Buckley (European Journal of Applied Physiology, 2013)

The relationship between antipsychotic D2 occupancy and change in frontal metabolism and working memory - Euitae Kim; Oliver D. Howes; Federico E. Turkheimer; Bo-Hyung Kim; Jae Min Jeong; Ji Who Kim; Jae Sung Lee; In-Jin Jang; Sang-Goo Shin; Shitij Kapur; Jun Soo Kwon (Psychopharmacology, 2013)

Associative blocking to reward-predicting cues is attenuated in ketamine users but can be modulated by images associated with drug use - Tom P. Freeman; Celia J. A. Morgan; Fiona Pepper; Oliver D. Howes; James M. Stone; H. Valerie Curran (Psychopharmacology, 2013)

A support system for assessing local vulnerability to weather and climate - Alex Coletti; Peter D. Howe; Brent Yarnal; Nathan J. Wood (Natural Hazards, 2013)

Conifer DBMagic: a database housing multiple de novo transcriptome assemblies for 12 diverse conifer species - W. Walter Lorenz; Savavanaraj Ayyampalayam; John M. Bordeaux; Glenn T. Howe; Kathleen D. Jermstad; David B. Neale; Deborah L. Rogers; Jeffrey F. D. Dean (Tree Genetics & Genomes, 2012)

The use of healthy volunteers instead of patients to inform drug dosing studies: a [11C]raclopride PET study - Euitae Kim; Oliver D. Howes; Bo-Hyung Kim; Kyung-Sang Yu; Jae Min Jeong; Jae Sung Lee; Su Jin Kim; In-Jin Jang; Jung Shin Park; Yong Gil Kim; Sang-Goo Shin; Federico E. Turkheimer; et al. (Psychopharmacology, 2011)

Mass-Spring Model for Simulation of Heart Valve Tissue Mechanical Behavior - Peter E. Hammer; Michael S. Sacks; Pedro J. del Nido; Robert D. Howe (Annals of Biomedical Engineering, 2011)

The peculiar heme pocket of the 2/2 hemoglobin of cold-adapted Pseudoalteromonas haloplanktis TAC125 - Barry D. Howes; Daniela Giordano; Leonardo Boechi; Roberta Russo; Simona Mucciacciaro; Chiara Ciaccio; Federica Sinibaldi; Maria Fittipaldi; Marcelo A. Martí; Darío A. Estrin; Guido di Prisco; Massimo Coletta; et al. (JBIC Journal of Biological Inorganic Chemistry, 2011)

Surface texture can bias tactile form perception - Masashi Nakatani; Robert D. Howe; Susumu Tachi (Experimental Brain Research, 2011)

Extended cardiolipin anchorage to cytochrome c: a model for protein–mitochondrial membrane binding - Federica Sinibaldi; Barry D. Howes; Maria Cristina Piro; Fabio Polticelli; Cecilia Bombelli; Tommaso Ferri; Massimo Coletta; Giulietta Smulevich; Roberto Santucci (JBIC Journal of Biological Inorganic Chemistry, 2010)

Do estuaries pose a toxic contamination risk for wading birds? - J. T. Smith; L. A. Walker; R. F. Shore; S. E. A. le V. dit Durell; P. D. Howe; M. Taylor (Ecotoxicology, 2009)

Salt marshes and eutrophication: An unsustainable outcome - R. Eugene Turner; Brian L. Howes; John M. Teal; Charles S. Milan; Erick M. Swenson; Dale D. Goehringer‐ Tonerb (Limnology and Oceanography, 2009)
Most plant production by emergent coastal marshes occurs belowground. This belowground production adds to the accumulation of organic matter sustaining salt marshes as sea level rises, thus preventing excessive flooding, eventual plant death, and habitat loss. The ubiquitous nutrient enrichment of coastal salt marshes stimulating aboveground plant growth may result in higher rates of inorganic matter accumulation that compensates for marsh flooding caused by sea level rise. Results from several short‐term experiments, however, demonstrate that root and rhizome biomass and carbon accumulation is reduced with nutrient enrichment, suggesting that eutrophication of coastal waters may not be a compensatory counterbalance to the effects of global sea level rise on salt marshes. We show that the net effects of 36 yr of nutrient enrichment in replicated field experiments do not lead to higher organic or inorganic accumulation. Enrichment reduces organic matter belowground and may result in a significant loss in marsh elevation equivalent to about half the average global sea level rise rates. Sustaining and restoring coastal emergent marshes is more likely if they receive less, not more, nutrient loading.

Cigarette smoking, body mass index, gastro-esophageal reflux disease, and non-steroidal anti-inflammatory drug use and risk of subtypes of esophageal and gastric cancers by P53 overexpression - Jonine D. Figueroa; Mary Beth Terry; Marilie D. Gammon; Thomas L. Vaughan; Harvey A. Risch; Fang-Fang Zhang; David E. Kleiner; William P. Bennett; Christine L. Howe; Robert Dubrow; Susan T. Mayne; Joseph F. Fraumeni; et al. (Cancer Causes & Control, 2009)

Dynamics of Campylobacter colonization of a natural host, Sturnus vulgaris (European Starling) - F. M. Colles; N. D. McCarthy; J. C. Howe; C. L. Devereux; A. G. Gosler; M. C. J. Maiden (Environmental Microbiology, 2009)
Summary Wild European Starlings ( Sturnus vulgaris ) shed Campylobacter at high rates, suggesting that they may be a source of human and farm animal infection. A survey of Campylobacter shedding of 957 wild starlings was undertaken by culture of faecal specimens and genetic analysis of the campylobacters isolated: shedding rates were 30.6% for Campylobacter jejuni , 0.6% for C. coli and 6.3% for C. lari. Genotyping by multilocus sequence typing (MLST) and antigen sequence typing established that these bacteria were distinct from poultry or human disease isolates with the ST‐177 and ST‐682 clonal complexes possibly representing starling‐adapted genotypes. There was seasonal variation in both shedding rate and genotypic diversity, both exhibiting a maximum during the late spring/early summer. Host age also affected Campylobacter shedding, which was higher in younger birds, and turnover was rapid with no evidence of cross‐immunity among Campylobacter species or genotypes. In nestlings, C. jejuni shedding was evident from 9 days of age but siblings were not readily co‐infected. The dynamics of Campylobacter infection of starlings differed from that observed in commercial poultry and consequently there was no evidence that wild starlings represent a major source of Campylobacter infections of food animals or humans.

Predicting body temperature and activity of adult Polyommatus icarus using neural network models under current and projected climate scenarios - P. D. Howe; S. R. Bryant; T. G. Shreeve (Oecologia, 2007)

Photopigment spectral absorbance of Lake Malaŵi cichlids - R. Jordan; K. Kellogg; D. Howe; F. Juanes; J. Stauffer; E. Loew (Journal of Fish Biology, 2006)
To predict spectral sensitivity, microspectrophotometry (MSP) was used to measure absorbance of photoreceptor cells from 15 species of Lake Malaŵi cichlids. Each fish had one rod and at least three cone pigments. UV‐sensitive pigments were common, but spectral sensitivity did not clearly correlate with feeding mode or habitat.

Insights into the role of the histidines in the structure and stability of cytochrome c - Federica Sinibaldi; Barry D. Howes; M Cristina Piro; Paola Caroppi; Giampiero Mei; Franca Ascoli; Giulietta Smulevich; Roberto Santucci (JBIC Journal of Biological Inorganic Chemistry, 2006)

Estimating pollen flow using SSR markers and paternity exclusion: accounting for mistyping - G. T. SLAVOV; G. T. HOWE; A. V. GYAOUROVA; D. S. BIRKES; W. T. ADAMS (Molecular Ecology, 2005)
Highly informative genetic markers, such as simple sequence repeats (SSRs), can be used to directly measure pollen flow by parentage analysis. However, mistyping (i.e. false inference of genotypes caused by the occurrence of null alleles, mutations, and detection errors) can lead to substantial biases in the estimates obtained. Using computer simulations, we evaluated a direct method for estimating pollen immigration using SSR markers and a paternity exclusion approach. This method accounts for mistyping and does not rely on assumptions about the distribution of male reproductive success. If ignored, even minor rates of mistyping (1.5%) resulted in overestimating pollen immigration by up to 150%. When we required at least two mismatching loci before excluding candidate fathers from paternity, the resulting pollen immigration estimates had small biases for rates of mistyping up to 4.5%. Requiring at least three mismatches for exclusion was needed to minimize the upward biases of pollen immigration caused by rates of mistyping up to 10.5%. The minimum number of highly variable SSR loci needed to minimize cryptic gene flow and obtain reliable estimates of pollen immigration varied from five to seven for a sampling scheme applicable to most conifers (i.e. when paternal haplotypes can be unambiguously determined). Between five and nine highly variable SSR loci were needed for a more general sampling scheme that is applicable to all diploid seed plants. With moderately variable SSR markers, consistently accurate estimates of pollen immigration could be obtained only for rates of mistyping up to 4.5%. We developed the pollen flow ( pfl ) computer program which can be used to obtain unbiased and precise estimates of pollen immigration under a wide range of conditions, including population sizes as large as 600 parents and mistyping rates as high as 10.5%.

The use of cover crops in cereal-based cropping systems to control nitrate leaching in SE England - A. J. Macdonald; P. R. Poulton; M. T. Howe; K. W. T. Goulding; D. S. Powlson (Plant and Soil, 2005)

Glycemic index, glycemic load, and pancreatic cancer risk (Canada) - Stephanie A. N. Silvera; Thomas E. Rohan; Meera Jain; Paul D. Terry; Geoffrey R. Howe; Anthony B. Miller (Cancer Causes & Control, 2005)

The 40s ?-loop plays a critical role in the stability and the alkaline conformational transition of cytochrome c - Paola Caroppi; Federica Sinibaldi; Elisa Santoni; Barry D. Howes; Laura Fiorucci; Tommaso Ferri; Franca Ascoli; Giulietta Smulevich; Roberto Santucci (JBIC Journal of Biological Inorganic Chemistry, 2004)

Ultraviolet reflectivity in three species of Lake Malaŵi rock‐dwelling cichlids - R. Jordan; K. Kellogg; F. Juanes; D. Howe; J. Staufferals; E. Loew; G. Losey (Journal of Fish Biology, 2004)
The body colouration extending into ultraviolet wavelengths in three species of Lake Malaŵi rock‐dwelling cichlids, Metriaclima zebra , Metriaclima benetos and Metriaclima barlowi was quantified. All three species were ultraviolet reflective with interspecific differences in reflectivity. In addition, individuals were able to behaviourally mediate their reflectivity.

The conservation of the belted beauty Lycia zonaria britannica (Lepidoptera, Geometridae) in the United Kingdom - M.A. Howe; D. Hinde; D. Bennett; S. Palmer (Journal of Insect Conservation, 2004)

Anion concentration modulates the conformation and stability of the molten globule of cytochrome c - Federica Sinibaldi; Barry D. Howes; Giulietta Smulevich; Chiara Ciaccio; Massimo Coletta; Roberto Santucci (JBIC Journal of Biological Inorganic Chemistry, 2003)

Experimental investigation of taxon‐specific response of alkaline phosphatase activity in natural freshwater phytoplankton - K. Rengefors; K. C. Ruttenberg; C. L. Haupert; C. Taylor; B. L. Howes; D. M. Anderson (Limnology and Oceanography, 2003)
It is widely accepted that alkaline phosphatase activity (APA) is an efficient indicator of phosphate limitation in freshwater phytoplankton communities. In this study, we investigated whether the response in APA to phosphate limitation differs among the taxa in a mixed phytoplankton assemblage. We used the new enzyme‐labeled fluorescence (ELF) technique, which allows microscopic detection of phosphate limitation in individual cells of multiple species. The most prominent findings of this study were that alkaline phosphatase (AP) was induced in many, but not all taxa and that different taxa, as well as different cells within a single taxon, experienced different degrees of phosphate stress under the same environmental conditions. Our approach was to manipulate the limiting nutrient in a natural freshwater phytoplankton community by incubating lake water in the laboratory. We induced nitrogen (N) or phosphate limitation through additions of inorganic nutrients. Both the ELF assay and bulk APA indicated that the lake phytoplankton were not phosphate limited at the start of the experiment. During the experiment, several chlorophyte taxa (e.g., Eudorina and an unidentified solitary spiny coccoid) were driven to phosphate limitation when inorganic N was added, as evidenced by a higher percentage of ELF‐labeled cells relative to controls, whereas other chlorophyte taxa such as Actinastrum and Dictyosphaerium were not phosphate stressed under these conditions. In the phosphate‐limited treatments, little or no ELF labeling was observed in any cyanobacterial taxa. Furthermore, all taxa observed after the ELF labeling procedure (

The research potential of tissue from a cadaveric donor - Christopher Womack; Neil M. Gray; Lesley J. Howes; Michael D. Harris (Cell and Tissue Banking, 2002)

Diet and benign ovarian tumors (United States) - Julie A. Britton; Carolyn Westhoff; Geoffrey Howe; Marilie D. Gammon (Cancer Causes & Control, 2000)

Formation of two types of low-spin heme in horseradish peroxidase isoenzyme A2 at low temperature - B. D. Howes; A. Feis; C. Indiani; M. P. Marzocchi; G. Smulevich (JBIC Journal of Biological Inorganic Chemistry, 2000)

Geological and Historical Investigation of the 1650 Mt. Columbo (Thera Island) Eruption and Tsunami, Aegean Sea, Greece - D. T. M. Dominey-Howes; G. A. Papadopoulos; A. G. Dawson (Natural Hazards, 2000)

Variation in quality and decomposability of red oak leaf litter along an urban-rural gradient - M. M. Carreiro; K. Howe; D. F. Parkhurst; R. V. Pouyat (Biology and Fertility of Soils, 1999)

Effects of plant species richness on invasion dynamics, disease outbreaks, insect abundances and diversity - J.M.H. Knops; D. Tilman; N.M. Haddad; S. Naeem; C.E. Mitchell; J. Haarstad; M.E. Ritchie; K.M. Howe; P.B. Reich; E. Siemann; J. Groth (Ecology Letters, 1999)
Declining biodiversity represents one of the most dramatic and irreversible aspects of anthropogenic global change, yet the ecological implications of this change are poorly understood. Recent studies have shown that biodiversity loss of basal species, such as autotrophs or plants, affects fundamental ecosystem processes such as nutrient dynamics and autotrophic production. Ecological theory predicts that changes induced by the loss of biodiversity at the base of an ecosystem should impact the entire system. Here we show that experimental reductions in grassland plant richness increase ecosystem vulnerability to invasions by plant species, enhance the spread of plant fungal diseases, and alter the richness and structure of insect communities. These results suggest that the loss of basal species may have profound effects on the integrity and functioning of ecosystems.

A review of boron effects in the environment - Paul D. Howe (Biological Trace Element Research, 1998)

The relationship between dietary fat intake and risk of colorectal cancer: evidence from the combined analysis of 13 case-control studies - Geoffrey R. Howe; Kristan J. Aronson; Enrique Benito; Roberto Castelleto; Jacqueline Cornée; Stephen Duffy; Richard P. Gallagher; José M. Iscovich; Jiao Deng-ao; Rudolf Kaaks; Gabriel A. Kune; Susan Kune; et al. (Cancer Causes & Control, 1997)

Interactions between coot (Fulica atra) and submerged macrophytes: the role of birds in the restoration process - Martin R. Perrow; J. Hans Schutten; John R. Howes; Tim Holzer; F. Jane Madgwick; Adrian J. D. Jowitt (Hydrobiologia, 1997)

Biological components of Sites of Special Scientific Interest in Wales - T. H. Blackstock; D. P. Stevens; E. A. Howe (Biodiversity and Conservation, 1996)

A recombinant fowlpox virus that expresses the VP2 antigen of infectious bursal disease virus induces protection against mortality caused by the virus - C. D. Bayliss; R. W. Peters; Jane K. A. Cook; R. L. Reece; K. Howes; M. M. Binns; M. E. G. Boursnell (Archives of Virology, 1991)

Effect of carbon source on enzymes involved in glycerol metabolism inNeurospora crassa - Gary D. Tom; M. Viswanath-Reddy; H. Branch Howe (Archives of Microbiology, 1978)

Mouse leukaemia, a dichotomy of virus neutralizing and cytotoxic antibodies - J. G. Sinkovics; C. C. Shullenberger; C. D. Howe; Barbara A. Bertin (Archives of Virology, 1966)